2007
DOI: 10.3402/rlt.v15i2.10916
|View full text |Cite
|
Sign up to set email alerts
|

Methodological issues in using sequential representations in the teaching of writing

Abstract: This study looks at a specific application of Ainsworth's conceptual framework for learning with multiple representations in the context of using multiple sequential graphic organizers that are student-generated for a process-writing task. Process writing refers to writing that consists of multiple drafts. It may be a process of re-writing without feedback or re-writing based on feedback where the teacher or peers will provide feedback on the original draft and then the students will revise their writing based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Naqbi, (2011) in her study concluded that "mind mapping helped students plan and organize their ideas for writing tasks under conditions of examination." (p.120) Meanwhile, Lee et al, (2007) in their study noticed that "good writers should have the choice to mind map the ideas for the essay the author intends to write on one piece of paper while poor writers should have the option to map their ideas one stage at a time" (p.139). On the other hand, Negari (2011) reported that "mapping strategy had a positive effect on English as a foreign language (EFL) learners' writing achievements"(p.299).…”
Section: Types Of Assessment In Narrative Writingmentioning
confidence: 99%
“…Naqbi, (2011) in her study concluded that "mind mapping helped students plan and organize their ideas for writing tasks under conditions of examination." (p.120) Meanwhile, Lee et al, (2007) in their study noticed that "good writers should have the choice to mind map the ideas for the essay the author intends to write on one piece of paper while poor writers should have the option to map their ideas one stage at a time" (p.139). On the other hand, Negari (2011) reported that "mapping strategy had a positive effect on English as a foreign language (EFL) learners' writing achievements"(p.299).…”
Section: Types Of Assessment In Narrative Writingmentioning
confidence: 99%